2020
DOI: 10.3390/su12239932
|View full text |Cite
|
Sign up to set email alerts
|

Are Central Government Rules Okay? Assessing the Hidden Costs of Centralised Discipline for Municipal Borrowing

Abstract: In the EU, the specialty municipal banks have been the traditional funding source besides tax sharing and governmental transfers for Local Governments (LGs). With the decentralization process, LGs experienced different market-based options so that banks were no longer the only source of funding. However, with the onset of the Eurozone crisis, public sector debt is no more risk-free, and the cost of borrowing became unstable over time. To minimise such risks, Central Governments forced LGs to adopt general prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Secondly, the research findings demonstrated that the program contributed to enhanced accountability among village officials (Chandra et al, 2022;Eltrudis & Monfardini, 2020;Pariyasiri, 2022;Senshaw & Twinomurinzi, 2022). With digital records and a systematic tracking system in place, it became easier to monitor and evaluate the use of village funds.…”
Section: Discussionmentioning
confidence: 94%
“…Secondly, the research findings demonstrated that the program contributed to enhanced accountability among village officials (Chandra et al, 2022;Eltrudis & Monfardini, 2020;Pariyasiri, 2022;Senshaw & Twinomurinzi, 2022). With digital records and a systematic tracking system in place, it became easier to monitor and evaluate the use of village funds.…”
Section: Discussionmentioning
confidence: 94%
“…The literature (Ter-Minassian and Craig, 1997;Bailey et al, 2009;2012;Cepiku and Mussari, 2010;Eltrudis and Monfardini, 2020) has identified four models for the governance of municipal borrowing to consider the contextual differences and differences in control approaches: the market discipline, the local political discipline, the centralised discipline, and the professional discipline. The centralised discipline and control model postulates the need for bureaucratic controls and relies on detailed rules that LGs must meet for them to borrow.…”
Section: Financial Autonomy Between Decentralisation and Recentraliza...mentioning
confidence: 99%
“…As a result, the European municipal bond market is smaller than the sovereign bond market (Medda and Cocconcelli, 2018). Moreover, it is particularly underdeveloped in unitary countries because adopting the centralised discipline and control model generates higher and hidden costs for the LGs that borrow from the financial markets (Eltrudis and Monfardini, 2020). Municipal bonds' spreading as an alternative to bank lending was hampered by the start of the European Union's Stability and Growth Pact, especially in unitary countries that preferred the bank lending channel over bonds as a source of debt funding (Peterson, 2003).…”
Section: Financial Autonomy Between Decentralisation and Recentraliza...mentioning
confidence: 99%
See 1 more Smart Citation
“…The adjustment of bank risk-taking in response to economic fluctuations is an operational requirement, and the influence of the government on banks is also common in the world [41], but there are few studies combining the three factors. More importantly, different from the existing research background, the CCB and the city investment company (CIC) are enterprises with Chinese characteristics and are experiencing the reform wave of economic and financial system.…”
Section: Literature Reviewmentioning
confidence: 99%